Effects of Mechanical Alloying on Sintering Behavior of Tungsten Carbide-Cobalt Hard Metal System - Gezerman, Ahmet Ozan; Çorbacıoglu, Burcu Didem (Advances in materials science and engineering, 2017)
During the last few years, efforts have been made to improve the properties of tungsten carbides (WCs) by preparing composite materials. In this study, we prepared WC particles by mechanical alloying and investigated the effects of mechanical alloying conditions, such as mechanical alloying time and mechanically alloyed powder ratio, on the properties of 94WC-6Co. According to experimental studies, increasing the mechanical alloying time causes an increase in the density of tungsten carbide samples and a decrease of crystal sizes and inner strength of the prepared materials. With the increase of mechanical alloying time, fine particle concentrations of tungsten carbide samples have increased. It is observed that increasing the mechanical alloying time caused a decrease of the particle surface area of tungsten carbide samples. Besides, the amount of specific phases such as Co3W3C and Co6W6C increases with increasing mechanical alloying time. As another subject of this study, increasing the concentration of mechanically alloyed tungsten carbides caused an increase in the densities of final tungsten carbide materials. With the concentrations of mechanically alloyed materials, the occurrence of Co6W6C and Co3W3C phases and the increase of crystallization are observed.